Storytelling to Teach Cultural Awareness: The Right Story at the Right Time (LEARNing Landscapes, 2014)
Stories contain the wisdom of the world, teaching cultural values, building community, celebrating cultural diversity, and preserving cultural identity. Where truth is suppressed, story is an instrument of epiphany and develops metaphorical understanding. A storytelling guild in Canada had been a cultural institution for 23 years, so when the center faced permanent closure, members were devastated. The purpose of this phenomenological study was to investigate the moment of this lived experience using interviews and focus groups. Findings indicated story strengthens content retention and language acquisition. These findings led to the development of a project focused on story-centered lessons for teachers.
Keywords: cultural diversity; story; wisdom; storytelling; phenomenology; lived experience; content retention; language acquisition